2020
DOI: 10.1111/petr.13798
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcome analysis of pediatric kidney transplant in posterior urethral valves children with or without pretransplant Mitrofanoff procedure

Abstract: Background: Urinary diversion using catheterizable channel among posterior urethral valve (PUV) patients may help to alleviate the functional concerns of the bladder on the allograft. Herein, we review our series of PUV patients undergoing renal transplants at a single institution to determine outcomes between those with and without pretransplant Mitrofanoff. Methods: PUV cases in our transplant database from 2000 to 2017 were identified. Data collected included clinical demographics, presentation of PUV, blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…On the other hand, Lopez Pereira et al did not find any significant differences in RT outcome in patients with or without BA (13), and other studies found good RT outcomes in patients with augmented bladders (14)(15)(16)(17)(18). Also, Rickard et al (19) identified similar RT outcomes in patients who did and did not undergo a Mitrofanoff procedure.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, Lopez Pereira et al did not find any significant differences in RT outcome in patients with or without BA (13), and other studies found good RT outcomes in patients with augmented bladders (14)(15)(16)(17)(18). Also, Rickard et al (19) identified similar RT outcomes in patients who did and did not undergo a Mitrofanoff procedure.…”
Section: Discussionmentioning
confidence: 93%
“…It is probable that patients that accomplish CIC via urethra or via the Mitrofanoff procedure have fewer possibilities to develop these behavior changes and to have a better urodynamic pattern in the follow-up ( 9 ). Rickard et al ( 19 ) found that implementing CIC via Mitrofanoff was associated with a delay in native renal function deterioration for a longer period, and that dialysis onset occurred at an older age compared to patients without Mitrofanoff. They postulated that this delay in renal failure was due to an improved compliance with CIC via Mitrofanoff and not via a sensate urethra.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the creation of a vesicostomy was statistically associated neither with a higher rate of febrile UTIs ( p = 0.088) nor with a poorer long-term kidney graft survival rate ( p = 0.3). There is, however, no evidence that catheterization via a stoma can reduce UTI episodes in patients undergoing CIC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bladder augmentation can be performed after kidney transplantation, with a similar complication rate when compared to preemptive augmentation (94,95). On the other hand, the general consensus is that graft survival is better when management of bladder dysfunction is optimized, for instance by the execution of the CIC (transurethral or via a catheterizable channel) (96).…”
Section: Renal Function Chronic (Ckd) and End Stage (Eskd) Kidney Dis...mentioning
confidence: 99%